Whose Time Is It? Book Presentation - Stamatia Portanova; Iain Chambers; Geoff Cox; Luciana Parisi; Tiziana Terranova (Media Theory)
On November 29th 2023, Whose Time Is It? Asocial Robots, Syncholonialism and Artificial Chronological Intelligence by Stamatia Portanova, was presented online by Iain Chambers, Luciana Parisi and Tiziana Terranova, in conversation with the author. The event was introduced by Geoff Cox, one of the two editors, together with Jacob Lund of the series The Contemporary Condition, in which the book was published. After a short introduction of the main themes of the book, this article provides for a transcript of the conversation.